2004
DOI: 10.1111/j.1365-2109.2004.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of blue shrimp Litopenaeus stylirostris (Perez-Farfante & Kensley, 1997) to dietary cadaverine supplementation

Abstract: Recent studies on salmon and shrimp have shown that reduced feed intake and growth caused by the consumption of low-quality ¢sh meals, manufactured from spoiled ¢sh, were not due to the presence of biogenic amines. Moreover, an improvement in weight gain was seen in blue shrimp fed a diet supplemented with cadaverine plus histamine. It was not clear, however, if this e¡ect was due to the consumption of histamine or cadaverine. The objective of the current experiment was to investigate the e¡ect of dietary cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In rabbits, histamine (10 −3 M) was found to stimulate pancreatic trypsinogen secretion from in vitro isolated rabbit pancreas preparations, but high concentrations (10 −2 M) of histamine are not unlike (Liebow and Franklin 1982 ). A similar effect of histamine was also found in the growth of blue shrimp (Tapia-Salazar et al 2004 ), immunity of crabs (Zhao et al 2012 ) and liver function of rabbits (Tripathi et al 2012 ). In these animals, the maximum effect of histamine is not the highest concentration but the lower concentration.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In rabbits, histamine (10 −3 M) was found to stimulate pancreatic trypsinogen secretion from in vitro isolated rabbit pancreas preparations, but high concentrations (10 −2 M) of histamine are not unlike (Liebow and Franklin 1982 ). A similar effect of histamine was also found in the growth of blue shrimp (Tapia-Salazar et al 2004 ), immunity of crabs (Zhao et al 2012 ) and liver function of rabbits (Tripathi et al 2012 ). In these animals, the maximum effect of histamine is not the highest concentration but the lower concentration.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, different animals may have their own special sensitivity to different level of histamine. Some researchers reported that high mortalities have been observed in poultry and mysis with dietary histamine supplementation (Harry et al 1975 ; Osuna 1985 ; Yang et al 2010 ), while histamine supplementation had no influence on shrimp and rainbow trout mortality (Fairgrieve et al 1998 ; Tapia-Salazar et al 2004 ), what’s more, histamine improves survival of mice (Hornyak et al 2005 ). Similar species differences in sensitivity to histamine have been demonstrated by mammals in studying gastric acid and pepsinogen secretion (Liebow and Franklin 1982 ), but no explanation was found for a correlation between histamine and sensitivity among species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that cadaverine at 2,000 mg/kg in a diet with 5% fishmeal acts as a good attractant. Tapia‐Salazar, Smith, Harris, Cruz‐Suárez, and Ricque‐Marie () worked with the blue shrimp, L. stylirostris , of 50 to 108 mg initial BW. They evaluated the dietary supplementation of cadaverine (0, 500, 1,100, 2,300, 3,500, and 4,600 mg/kg) for 28 days in 10‐L fiberglass tanks.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mendoza et al (1997) reported that even 0.2% of cadaverine acted as a potential attractant in Macrobrachium rosenbergii fed a diet containing 5% fishmeal. But, later Tapia-Salazar et al (2004) in L. stylirostris, failed to show a similar effect even after supplementing 0.46% of cadaverine. However, when it was supplemented with histamine it showed an enhanced growth performance in the species.…”
Section: Efficacy Of Chemoattractants In Shrimp Aquaculturementioning
confidence: 90%